Analisis Minat Penggunaan Cashless Payment dalam Transaksi Jual Beli Selama Pandemi pada UMKM Kota Malang - Ananda Yuke Wahyu Putra Pratama; Intan Sartika Eris Maghfiroh; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Cashless Payment is an innovation from the development of digital services in facilitating the transaction process. The benefits of digital payments that are felt by users are getting convenience in using the system, getting evidence of transaction results, practicality in conducting transactions, and the level of security of the system related to the transaction process. This study was conducted to ease identify the effect of interest in use of perceived ease to use and perceived usefulness. The digital payment applications studied in this study are OVO, GoPay, ShopeePay, Dana, and LinkAja. The sampling technique used was purposive sampling technique on two categories of UMKM respondents and buyers. Through questionnaire statements distributed through Google Form, 130 respondents were obtained from UMKM and 135 respondents were buyers. From the two categories of respondents, it is known that the variableso perceive ease to use and perceived usefulness have an influence on interest in using non-cash payment applications. It is known that in both categories of respondents there is a partial or simultaneous influence on interest in use from perceptions of ease of use and perceptions of usefulness with the results of the significance value below 0.05. From the results of the regression model equation, the intention to use of digital payments will increase positively according to the regression coefficient value getting a positive value, if it is known from perception ease to use of and perceived usefulness has increased positively.